The changing role of substances: trends, characteristics of individuals and prior healthcare utilization among individuals with accidental substance-related toxicity deaths in Ontario Canada. - Shaleesa Ledlie; Alice Holton; Pamela Leece; Bisola Hamzat; Joanna Yang; Gillian Kolla; Nikki Bozinoff; Rob Boyd; Mike Franklyn; Ashley Smoke; Paul Newcombe; Tara Gomes (PLoS ONE)
Objective To investigate trends and the circumstances surrounding fatal substance-related toxicities directly attributed to alcohol, stimulants, benzodiazepines or opioids and combinations of substances in Ontario, Canada. Methods We conducted a population-based cross-sectional study of all accidental substance-related toxicity deaths in Ontario, Canada from January 1, 2018 to June 30, 2022. We reported monthly rates of substance-related toxicity deaths and investigated the combination of substances most commonly involved in deaths. Demographic characteristics, location of incident, and prior healthcare encounters for non-fatal toxicities and substance use disorders were examined. Results Overall, 10,022 accidental substance-related toxicity deaths occurred, with the annual number of deaths nearly doubling between the first and last 12 months of the study period (N = 1,570-2,702). Opioids were directly involved in the majority of deaths (84.1%; N = 8,431), followed by stimulants (60.9%; N = 6,108), alcohol (13.4%; N = 1,346) and benzodiazepines (7.8%; N = 782). In total, 56.9% (N = 5,698) of deaths involved combinations of substances. Approximately one-fifth of individuals were treated in a hospital setting for a substance-related toxicity in the past year, with the majority being opioid-related (17.4%; N = 1,748). Finally, 60.9% (N = 6,098) of people had a substance use disorder diagnosis at time of death. Conclusions Our study shows not only the enormous loss of life from substance-related toxicities but also the growing importance of combinations of substances in these deaths. A large proportion of people had previously interacted within an hospital setting for prior substance-related toxicity events or related to a substance use disorder, representing important missed intervention points in providing appropriate care.